Preclinical Evaluation of the GRPR-Targeting Antagonist RM26 Conjugated to the Albumin-Binding Domain for GRPR-Targeting Therapy of Cancer - Ayman Abouzayed; Hanna Tano; Ábel Nagy; Sara S. Rinne; Fadya Wadeea; Sharmishtaa Kumar; Kristina Westerlund; Vladimir Tolmachev; Amelie Eriksson Karlström; Anna Orlova (Pharmaceutics, 2020)
The targeting of gastrin-releasing peptide receptors (GRPR) was recently proposed for targeted therapy, e.g., radiotherapy. Multiple and frequent injections of peptide-based therapeutic agents would be required due to rapid blood clearance. By conjugation of the GRPR antagonist RM26 (D-Phe-Gln-Trp-Ala-Val-Gly-His-Sta-Leu-NH2) to an ABD (albumin-binding domain), we aimed to extend the blood circulation of peptides. The synthesized conjugate DOTA-ABD-RM26 was labelled with indium-111 and evaluated in vitro and in vivo. The labelled conjugate was stable in PBS and retained specificity and its antagonistic function against GRPR. The half-maximal inhibitory concentration (IC50) of natIn-DOTA-ABD-RM26 in the presence of human serum albumin was 49 ± 5 nM. [111In]In-DOTA-ABD-RM26 had a significantly longer residence time in blood and in tumors (without a significant decrease of up to 144 h pi) than the parental RM26 peptide. We conclude that the ABD-RM26 conjugate can be used for GRPR-targeted therapy and delivery of cytotoxic drugs. However, the undesirable elevated activity uptake in kidneys abolishes its use for radionuclide therapy. This proof-of-principle study justified further optimization of the molecular design of the ABD-RM26 conjugate.